Hubungan Antara Kualitas Tidur dan Stres Kerja dengan Kelelahan Kerja pada Petugas Pemadam Kebakaran - Annisa Nurul Izza; Tri Martiana (Media Gizi Kesmas, 2023)
Background: Firefighting is one of the jobs that have a high risk of experiencing work fatigue. This is because firefighters are required to be able to complete their work optimally and carefully. Firefighters who experience work stress and bad sleep quality can increase the risk of work fatigue. Objectives: This study aims to determine the relationship between sleep quality and work stress with work fatigue in firefighters at the East Jakarta Fire and Rescue Service. Methods: This study is an analytical observational study with a cross-sectional study approach. The sample in this study was determined using a simple random sampling technique on the workers of the Sub-Unit Members of the Fire and Rescue Service at the East Jakarta Fire Department with various criteria, so that 40 people were obtained. Results: Data analysis using Chi Square and Rank Spearman analysis techniques showed that there was a significant relationship between sleep quality and work fatigue (p value = 0.027 < 0.05) and there was a significant relationship between work stress and work fatigue (sig. (2-tailed) = 0.000 < = 0.05). Conclusions: It was concluded that there is a relationship between sleep quality and work stress with work fatigue on firefighters of the East Jakarta Fire and Rescue Service Department.